Congruence relationships between the choice of major and stereotypes: The case for agribusiness programs within a business school setting. Issue 7 (3rd October 2022) - Magnier, Alexandre; Van Auken, Stuart; Palacios Rivera, Jamille
Abstract: The objective of this study is to explore the stereotypes that students have about agribusiness students. We seek to determine the nature of these stereotypes and how they compare relative to marketing and accounting students. Our intent is to reveal the degree of fit of the agribusiness major within a college of business, as personality congruence may influence the pursuit of a major within a business school framework. Our results show that stereotypes about agribusiness majors fall in between those of marketing and accounting students, which suggests that stereotypes would not appear to negatively affect enrollment within a business school setting.